Kontribusi Aktivis Mesjid Lautze 2 Bandung dalam Merangkul Mualaf Tionghoa Tahun 2016-2021 - Ilham Muhamad Nurjaman; Setia Gumilar (Jurnal Iman dan Spiritualitas, 2021)
Lautze 2 Mosque in Bandung was established in January 1997. The location of Lautze 2 Mosque is on Jl. Tamblong number 27 Bandung City. Lautze 2 Mosque is a branch of Lautze 1 Mosque in Jakarta. Lautze 2 Mosque in Bandung has its uniqueness, especially in the architecture of the building. Lautze 2 Mosque, conceptualized in the shape of a temple. The red, yellow, and gold paint colors that adorn the walls of the Lautze 2 Mosque reflect Chinese culture. In addition to the paint color, the ornaments that adorn the mosque also have a Chinese nuance. From 2016 to 2021, there were 151 who took the oath of faith at the Lautze 2 Mosque. In addition to religious activities, the Lautze 2 Mosque always held social programs. One of them is the iftar program and on the road a thousand dates. This activity was supported by various parties, one of which was the Salman Charity House. Not only Muslims who support this, but even many interfaith also donate to keep this activity. In writing this article, the theory used is the racial theory proposed by Murtadha Muttahari. According to him, the leading cause of historical progress is certain races.